Comparing the microhardness of a bulk-fill composite resin and a conventional nano-hybrid composite resin - حداد منذر (Latakia University Journal -Medical Sciences Series, 2023)
Composite was introduced in dentistry to improve the acrylic resin that replaced silicate cement, which had been the only cosmetic restorative material in dentistry since the 1940s. (Bunocore, 1955, using phosphorous acid, and (Bowen, 1963) improved the physical properties of acrylic resin by adding Bis-GMA monomers, where the addition of these monomers allowed the formation of polymers of linear chains. The first generations of chemical hardening composites suffered from the problem of discoloration and the need to mix two components, the base and the accelerator (Kinomoto et al., 1999). The surface hardness values of the composite are higher as the content of fillers increases (Eliades et al., 1987) The study showed higher values of surface hardness with a statistically significant difference for Tetric-N-Ceram composite compared to Tetric Bulk-Fill composite, where the percentage of filling for the first is 63.5% and 61.0%. % for the second (Alkurdi & Abboud, 2016). In the study (Saati et al., 2022) Tetric Bulk-Fill Composite had the lowest hardness values compared to Xtrafil and Filtek Z250 used in the study and this is consistent with our study.